Registration of oat cultivar 'Natty'. Issue 3 (31st August 2020) - Caffe‐Treml, M.; Hall, L.; Bauer, R.; Hall, N.; Kleinjan, J.; Graham, C.; Ingemansen, J. A.; Turnipseed, B.; Krishnan, P.
Abstract: The development of oat ( Avena sativa L.) cultivars with improved grain yield and excellent test weight is necessary to increase the profitability of oat production. 'Natty' (Reg. no. CV‐385, PI 676027) was developed by the South Dakota State University (SDSU) oat breeding program and was released in 2014. The pedigree of Natty is SD020701//SD030888/ND030349. Natty exhibited high grain yield potential and excellent test weight when evaluated in the South Dakota Crop Performance Testing Oat Variety Trials and in the Uniform Early Oat Performance Nursery. The grain of Natty is characterized by a large proportion of plump kernels and groats with low beta‐glucan and oil content. Natty is resistant to smut, moderately susceptible to susceptible to crown rust, and moderately tolerant to Barley yellow dwarf virus . Natty is a tall and early‐maturing cultivar suited for the production of oat grain for the feed market. Although its milling quality is good, the low beta‐glucan content of Natty is not desirable for the food market. Based on its height, Natty is also suited for straw production. Three of the oat cultivars released by SDSU were named after Lon Hall's grandchildren; Natty is one of them. Lon Hall was oat breeder at SDSU from 2001 to 2014.